Thinking biases and their role in persecutory delusions: A systematic review. Issue 12 (9th April 2022) - De Rossi, Giorgia; Georgiades, Anna
Abstract: Aim: Thinking biases are posited to be involved in the genesis and maintenance of delusions. Persecutory delusions are one of the most commonly occurring delusional subtypes and cause substantial distress and disability to the individuals experiencing them. Their clinical relevance confers a rationale for investigating them. Particularly, this review aims to elucidate which cognitive biases are involved in their development and persistence. Methods: MEDLINE, Embase, PsycINFO and Global Health were searched from the year 2000 to June 2020. A formal narrative synthesis was employed to report the findings and a quality assessment of included studies was conducted. Results: Twenty five studies were included. Overall, 18 thinking biases were identified. Hostility and trustworthiness judgement biases appeared to be specific to persecutory delusions while jumping to conclusions, self‐serving attributional biases and belief inflexibility were proposed to be more closely related to other delusional subtypes. While the majority of the biases identified were suggested to be involved in delusion maintenance, hostility biases, need for closure and personalizing attributional biases were believed to also have aetiological influences. Conclusions: These findings show that some cognitive biases are specific to paranoid psychosis and appear to be involved in the formation and/or persistence of persecutory delusions.